Risk in international finance - Yadav, Vikash (London ; New York : Routledge, 2008)
This book analyzes the evolution and impact of the concept of risk on processes of transnational banking and financial market regulation, as well as the externalities generated by speculative financial activity in emerging market economies.
Introduction -- Surfaces of inscription -- Theory of risk -- Theory of regulation -- Regulating risk -- The political arena -- Conclusion.
Includes bibliographical references (p. [148]-171) and index.
rpm 14/05/13
Loans
Keywords: International finance; Financial risk; Financial services industry -- Risk management